Does continuation of antifibrotics before lung transplantation influence post-transplant outcomes in patients with idiopathic pulmonary fibrosis?. (28th August 2021) - Zhu, Michael Z L; Huang, Joanna Yilin; Liu, David Hongwei; Snell, Gregory I
Summary: A best evidence topic was written according to a structured protocol. The question addressed was: 'Does continuation of antifibrotics before lung transplantation (LTx) influence post-transplant outcomes in patients with idiopathic pulmonary fibrosis (IPF) with regard to mortality, bronchial anastomotic dehiscence, reoperation for bleeding and wound complications, primary graft dysfunction or longer-term survival and allograft rejection?' A total of 261 articles were found using the reported search strategy, of which 7 represented the best evidence to answer the clinical question. Six out of 7 studies demonstrated equivalent post-transplant survival among IPF patients on antifibrotics before LTx compared with controls. Five out of 6 studies showed no increase in the risk of major bleeding, wound or bronchial anastomotic complications. One bi-institutional study found a higher incidence of early bronchial anastomotic dehiscence, but this difference was not statistically significant after longer term follow-up. In a study that only included IPF patients who underwent single LTx, a lower incidence of grade 3 primary graft dysfunction was reported in the antifibrotic group compared with controls. Overall, to date, only small ( N  < 40 in the antifibrotic group), non-risk-adjusted, retrospective observational studies have been published. Notwithstanding, the summation of available evidence suggests that, in IPF patients, continuation of antifibrotic therapy before LTx is likely safe, and the rates of perioperative bleeding, wound or bronchial anastomotic complications, as well as 30-day and 1-year survival, are similar to patients not on antifibrotics before LTx. Abstract : A best evidence topic was constructed according to a structured protocol.